Behaviour of RHS beam‐to‐column bolted steel connections. Issue 4 (November 2016) - dos Santos, Gabriel Barros; de Miranda Batista, Eduardo; de Araújo, Afonso Henrique Mascarenhas
Abstract: The connection concept is a key point in the design of steel structures which affects fabrication, erection procedures and the final costs. Welding processes have been extensively used for tubular trussed girders by combining shop welding with bolted flange solutions to facilitate straightforward connection procedures during erection. The present research addresses the behaviour of innovative beam‐to‐column bolted connections for steel rectangular hollow sections (RHS) which combine simplicity in fabrication and erection, favourable aesthetics for the case of visible structures and structural effectiveness. Four cruciform prototypes were tested under a static non‐reversible bending moment with different bolted conditions: i) non‐friction and ii) friction connection. The experimental results show that the proposed geometry with friction connections is able to develop a rigid elastic moment–rotation response up to usual loading conditions.